Current state of geoengineering - LUCZAK, Joshua (Institutional Knowledge at Singapore Management University, 2024)
There are, broadly speaking, three ways in which scientists and policymakers talk about responding to the anthropogenic climate change. We can mitigate the effects, adapt to it, or we can utilize geoengineering techniques to offset its harmful impacts. As it currently stands, most reasonable scientists, policymakers, and thinkers hold that some combination of adaptation together with an aggressive mitigation strategy is the most appropriate, all things considered, way to respond to the problem. Since we are already committed to some climate change, any response to the problem must include some kind of adaptation strategy. But, for a collection of reasons, aggressive mitigation has to be the focus of our policy response. It is the best, safest, and most fair way to resolve the problem in the long run. Despite this, talk of incorporating forms of geoengineering into our overall response strategy have grown in recent times. In light of this trend, this chapter provides an overview of geoengineering that is relevant for policymakers and lawmakers. This chapter describes the most common and influential geoengineering techniques that have been proposed and gives the reader a sense of where geoengineering techniques sit in the minds of scientists and policymakers. There is currently a dearth of laws and regulations that are directly aimed at ensuring the safe development, testing, and deployment of geoengineering techniques. There is also a lack of governance overseeing the research and development of these techniques. This chapter serves as a partial primer for anyone interested in wading into policy and legal issues surrounding geoengineering.